Bedah Buku Biografi Abah Lukmanul Hakim bin Haji Musthofa Al-Banjari (Tokoh Islam Kharismatik Enok Dalam Abad ke-XX) - A. Muthalib; Khairuddin Khairuddin; Edi Ardian; Edi Susrianto; Nurbaidi Nurbaidi (STAI Auliaurrasyidin Tembilahan, 2022)
Talking about the history of a scholar (Islamic figure) in this country always attracts attention from various groups to be studied and studied further, in order to take lessons from the sides of his life to be emulated, imitated or emulated in our families and communities wherever they are, because Scholars are heirs of the Prophets. The history of Abah Lukman can be summarized as follows: Abah Lukmanul Hakim was a Ulama from the land of Banjar who had studied Islam in the holy city of Mecca and then after he returned to Indonesia then madam (wandered) to Indragiri Riau around 1914. Abah Lukmanul Hakim had studied with Mr. Sapat in Hidayat Village. At that time Abah lived in Tekulai Hilir. He was one of the special students when he studied at Hidayat, because in general he had studied the books studied in the village when he was in Mecca, but he wanted to take